CLINICAL AND PARACLINICAL CHARACTERISTICS AND TREATMENT OUTCOMES OF THREATENED PRETERM LABOR AT NAM DINH OBSTETRICS AND GYNECOLOGY HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the clinical and paraclinical characteristics of patients with threatened preterm labor and to evaluate treatment outcomes at Nam Dinh Obstetrics and Gynecology Hospital in 2025.Methods: A retrospective descriptive study was conducted.Results: The success rate of ectopic pregnancy treatment with methotrexate was 82.5%. The study included 227 pregnant women diagnosed with threatened preterm labor. The mean maternal age was 27.9 ± 6.2 years, and the mean gestational age at admission was 31.8 ± 3.3 weeks. Most participants had no history of preterm birth (89%) and had not previously delivered at term (52%). The most common clinical symptoms were abdominal pain (93.8%) and vaginal bleeding (54.2%). The majority of cases presented with infrequent uterine contractions (< 1 contraction per 10 minutes, 93%), a closed cervix (81.9%), and a Bishop score < 4 (64.8%). Leukocytosis was observed in 56.4% of patients. The treatment success rate was high, reaching 94.3% after 48 hours and 92.1% after 7 days. Cervical dilation ≥ 2 cm, vaginal bleeding, and advanced maternal age were associated with a reduced likelihood of successful pregnancy prolongation. Progesterone and smooth muscle relaxants were associated with improved treatment outcomes.Conclusion: The common clinical manifestations of threatened preterm labor include abdominal pain, infrequent uterine contractions, and minimal cervical changes. The rate of successful pregnancy prolongation at Nam Dinh Obstetrics and Gynecology Hospital was 94.3% after 48 hours and 92.1% after 7 days. Factors such as vaginal bleeding, cervical dilation, maternal age, and medication use were associated with treatment outcomes in threatened preterm labor.
Keywords: Threatened preterm labor, treatment outcomes.